2020
DOI: 10.1186/s12885-020-07148-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adenocarcinoma and adenosquamous carcinoma prognoses in Chinese patients with FIGO stage IB-IIA cervical cancer following radical surgery

Abstract: Background: To compare adenocarcinoma (AC) and adenosquamous carcinoma (ASC) prognoses in patients with FIGO stage IB-IIA cervical cancer who underwent radical hysterectomy. Methods: We performed a retrospective analysis of 240 patients with AC and 130 patients with ASC. Kaplan-Meier curves, Cox regression models, and log-rank tests were used for statistical analysis. Results: Patients with ASC had higher frequencies of lymphovascular space invasion (LVSI) and serum squamous cell carcinoma antigen (SCC-Ag) > 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
3
20
1
Order By: Relevance
“…Zhou et al 14 found that patients with ADC were more likely to be well and moderately differentiated, while more ASC patients were poorly and undifferentiated. Zhang et al 10 recently found that, compared with ADC patients, patients with ASC tended to be older and have higher frequencies of LVSI and serum squamous cell carcinoma antigen (SCC-Ag) greater than 5 ng/mL. However, in our study, the incidence of pelvic lymph node metastasis in patients with ADC was higher than that in patients with ASC.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Zhou et al 14 found that patients with ADC were more likely to be well and moderately differentiated, while more ASC patients were poorly and undifferentiated. Zhang et al 10 recently found that, compared with ADC patients, patients with ASC tended to be older and have higher frequencies of LVSI and serum squamous cell carcinoma antigen (SCC-Ag) greater than 5 ng/mL. However, in our study, the incidence of pelvic lymph node metastasis in patients with ADC was higher than that in patients with ASC.…”
Section: Discussioncontrasting
confidence: 78%
“…Early studies have shown that compared with ADC patients, ASC patients tended to have a lower 5-year DFS rate and shorter interval of disease recurrence. 8,9 However, Zhang et al 10 recently compared the outcome between ADC and ASC patients, which showed no significant prognostic difference.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, ASC type group includes glassy cell carcinoma and mucoepidermoid carcinoma. 12,[26][27][28][29][30] Data confirm the monoclonal origin of ASC, differentiating it as a distinct biological entity from both SCC and AC. 31 Precursors to this carcinoma type are high-grade squamous intraepithelial lesion (HSIL) and adenocarcinoma in situ (ACIS) with frequent detection of Human Papilloma Virus types 16 and 18 related to them.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding cervical ADC, limited reports are available for serum tumor markers, including carbohydrate antigen-125 (CA125), CA 19-9, and carcinoembryonic antigen [ 9 10 11 12 ]. Among aforementioned markers, CA125 has been established as an important marker in the diagnosis and monitoring of other gynecologic tumors, such as ovarian and endometrial cancer [ 12 13 14 15 ]. Although several reports have noted its significance in cervical cancer, the reports included heterogeneous groups of patients, including those with both ADC and adenosquamous cell carcinoma, and patients treated with either definitive RT or adjuvant RT.…”
Section: Introductionmentioning
confidence: 99%